THE PENAMBAHAN LATIHAN PENGUTAN DENGAN EN TREE PADA INTERVENSI ULTRA SOUND DAN TENS UNTUK MENGURANGI NYERI PADA PENDERITA OSTEOARTHRITIS LUTUT DI RSUP SANGLAH DENPASAR. - Ady Pranatha, I Nyoman (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 3 (2013): Majalah Ilmiah Fisioterapi Indonesia, 2013)
Osteoarthritis genu is a condition of degenerative deasis in the knee joint, can cause by many factors such as trauma and over weight and the characteristic is the damage of the cartilage in the joint. Adding strengthening exercise with ENTRÉE in ultrasound and Tens intervention is for reduce the pain for people who have condition osteoarthritis genu.The purpose of the experiment is to know the affectivity of adding strengthening exercise with ENTRÉE in intervention ultrasound and Tens to reduce osteoarthritis genu pain at patient in RSUP Sanglah Denpasar. In this situation we experimenters using randomized pre list and post test group design . The population on this experiment and patients who come to RSUP Sanglah Denpasar with osteoarthritis  condition. The sample we got are 20 patients where divide to tow group and experiment group. Sample are chose by technique randomized sampling.Collecting   data are using a questioner which contain demography  of patient and pain scale of patient. The data that we got than we analyzed using Shapiro wilk  test for the distribution of sample and levenes test for homogeneity of sample chose how test have the same result witches p = 0,000 ( p < 0,05 ). It’s mean the data are distribution normally and homogeneity. After we know the result we chose the paired sample  t test and wilcoxon test for first hypothesis and second hypothesis. This test shown that the p= 0,000 (p<0,05). It is indicate the both hypothesis are true. After that we use the independent sample t test and mann whitney test foe exam the third hypothesis and the result is p = 0,000 (p = 0,05). It’s mean is adding strengthening exercise with ENTRÉE in ultrasound and tens intervention more affective to reduce the pain in osteoarthritis genu condition.
Keywords: EN TREE, ultrasound, Tens, osteoarthritis genu, reduce of pain.